INTEGRATING ISLAMIC ECONOMIC PRINCIPLES INTO SOCIAL HEALTH INSURANCE: INSIGHTS FROM THE INDONESIAN EXPERIENCE - Badeges, Abdul Malik; Ab Rahman, Asmak; Biancone , Paolo; Calandra , Davide (Jurnal Syariah, 2024)
This study investigates the intersection of Islamic economics and Indonesia’s social health insurance, BPJS Kesehatan, aiming to enhance its sustainability and equity. By examining BPJS through Islamic economic principles, particularly the concept of wakalah (agency), the research explores how this framework can improve the system’s operational efficiency and fairness. Wakalah, in this context, signifies the appointment of BPJS as an agent (wākil) by participants to manage healthcare funds according to Shariah principles, emphasizing trust, responsible fund management, and adherence to intended purposes like covering medical expenses. The study further develops a human development model grounded in Maqaṣid al-Shariah (objectives of Islamic law), incorporating exogenous factors like social justice and human rights alongside endogenous factors like education, health, and income. This model analyzes how integrating Islamic economic principles, including wakalah and the potential for a non-profit operational model promoting mutual cooperation, can contribute to more equitable and just healthcare outcomes within Indonesia’s unique cultural and religious context, contributing to the broader discourse on faith-based social welfare systems.